PENGGUNAAN BILYET GIRO (B/G) KOSONG DALAM TRANSAKSI PEMBAYARAN - Cisca Purnama Sari; Rahmat Ihya' (Fakultas Hukum dan Sosial Universitas Sunan Giri Surabaya, 2022)
Currently, the development of securities in Indonesia is related to business activities, not to mention the banking liberalization policy by the government in the form of policy packages in the banking sector. As a result of this policy, the number of banks and bank offices grew rapidly, accompanied by increased competition and the development of new “Financial Instruments” products, as well as the growing use of Money Market securities and banking documents. This study uses a normative juridical legal research method, which is carried out by examining the laws and regulations governing the problem of using bilyet giro as a means of payment. The use of blank bilyet giro in this payment transaction has a bad impact on business people, especially holders of blank bilyet giro. As a result, the holder of an empty bilyet giro is disadvantaged in trading because he does not get what he is entitled to. In trade relations or accounts payable, if one party has not fully paid its obligations or achievements, but has paid with a blank check or bilyet giro, then the problem is a default